Implementasi Pendidikan Karakter di Pondok Pensantren Darul Qur’an Sumbersari Kencong Kepung Kediri - Ahmad Fauzi (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Character education is essentially aiming to form a nation that is resilient, competitive, noble, moral, lively, bergotongroyong, patriotic, dynamic-developing, science-oriented and technology that all are imbued by Faith and Taqwa to the one true God based on Pancasila. Education in Pesantren plays a big role in character building in Indonesia. The boarding school has been proven as an institution that also forms the character and personality of the citizens of the nation. Pesantren is a sub-culture of Islam that is rooted in the Islamic culture in Indonesia. Pondok Pesantren Darul Qur'an (PPDQ) Sumbersari has a vision to build students ' character to provision a better and dignified life.